PHARMACOGNOSTICAL CHARACTERIZATION OF PHYLA NODIFLORA L. (VERBENACEAE): A VALUABLE MEDICINAL PLANT - Priya S, Evelyne; R, Ravindhran (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The objective of the present study was to evaluate the pharmacognostical and histochemical characters of Phyla nodiflora L. (Verbenaceae) an important medicinal plant. Methods: Pharmacognostical characters such as macroscopic and anatomical characters of root, stem and leaf were studied. Physico-chemical characteristics of crude drugs of aerial parts and root were determined. To localize various phytochemicals, histochemical studies were also determined. Results: Pharmacognostical studies helped in the identification and authentication of the plant material. Physico-chemical properties such as water soluble extractive value (21.44±0.009% w/w), alcohol soluble extractive (13.39±0.03% w/w), total ash (20.85±0.09% w/w), loss on drying (15.68±0.05% w/w) were calculated. Histochemical study indicated the presence of alkaloids, lignin, starch, proteins, lipids, phenolics, and tannins in the plant parts examined. Conclusion: This study revealed the pharmacognostical properties and characteristics of P. nodiflora, an important medicinal plant. The presence of alkaloids, lignin, starch, proteins, lipids, phenolics, and tannins in the plant parts can be attributed to the cytotoxic, antimicrobial, antiviral, and antifungal properties of P. nodiflora. Keywords: Phyla nodiflora, Microscopy, Pharmacognosy, Stomatal index, Histochemistry.